Comparison of Lactiplantibacillus plantarum isolates from the gut of mice supplemented with different types of nutrients: a genomic and metabolomic study - Wang, Ziyan; Zhang, Zhixuan; Shi, Qiuyue; Liu, Songyi; Wu, Qiaoli; Wang, Ze; Saiding, Emilaguli; Han, Jiaojiao; Zhou, Jun; Wang, Rixin; Su, Xiurong (Frontiers in Microbiology, 2023)
Many studies have focused on the influence of dietary supplements on gut microbiota composition, but limited research have reported their effects on specific bacterial species in the gut. Lactiplantibacillus plantarum is one of the most widely studied probiotics, with a wide range of sources and good environmental adaptability.In this study, in order to elucidate the adaptation strategies of L. plantarum to the gut of mice supplemented with carbohydrates, peptides and minerals, whole genome resequencing and intracellular metabolites detection were performed, and highfrequency mutant genes and differential metabolites were screened. The results suggested different types of dietary supplements do have different effects on L. plantarum from the gut of mice. Additionally, KEGG annotation unveiled that the effects of these dietary supplements on the gene level of L. plantarum primarily pertained to environmental information processing, while the differential metabolites were predominantly associated with metabolism. This study provided new perspectives on the adaptive mechanism of L. plantarum in response to the host's gut environment, suggesting that the diversity of the genome and metabolome of L. plantarum was correlated with dietary supplements. Furthermore, this study offered useful guidance in the effective utilization of dietary supplements.